Serine 7 of the RNA polymerase II CTD is specifically required for snRNA gene expression - Egloff, Sylvain (2007)
RNA polymerase II (pol II) transcribes genes encoding proteins and non-coding small nuclear (sn)RNAs. The carboxy-terminal domain (CTD) of the largest subunit of mammalian RNA polymerase II (pol II), comprising tandem repeats of the heptapeptide consensus tyr1ser2pro3thr4ser5pro6ser7, is required for expression of both gene types. Here, we show that mutation of ser7 to alanine causes a specific defect in snRNA gene expression. We also present evidence that phosphorylation of ser7 facilitates interaction with the snRNA gene-specific Integrator complex. These findings asign a biological function to this amino acid and highlight a gene type-specific requirement for a residue within the CTD heptapeptide, supporting the existence of a CTD code.